The Effects of the Madeung Tradition on the Nutritional Status of Postpartum Mothers in Alue Waki, Aceh - Arif Iskandar; Khori Suci Maifianti (Universitas Teuku Umar, 2021)
The high level of public belief and trust in the madeung tradition as a treatment for postpartum mothers is still widely found in traditional Acehnese communities, especially the Raja Ubit family – an indigenous community in Blang Tripa. Postpartum mothers are required to practice the madeung tradition in the form of restrictions on consuming certain types of food, in which this tradition must be carried out for 44 days. The purpose of this study was to find out the effects of the practice of the madeung tradition on the nutritional status of postpartum mothers. This study applied a descriptive-analytic design with a cross-sectional approach. The number of respondents in this study was 20 people. The results of the chi-squared test, Fisher’s exact test, and cross-tabulation between the nutritional status of postpartum mothers and the practice of the madeung tradition indicated the p-value of 0.545 (> 0.05). Therefore, it can be concluded that there is no significant influence between the nutritional status of postpartum mothers and the practice of the madeung tradition. Health officers from Alue Rambot Health Center are expected to run education programs for pregnant women about the good practice of the madeung tradition after the childbirth process based on health principles. Keywords: Madeung Tradition, Nutritional Status, Postpartum Mothers.